Uso de membranas de microfiltração e ultrafiltração para recuperação e concentração de amilase produzida em resíduo agroindustrial (manipueira) como substrato - Jesus, Mayara Vieira de (2019)
Amylases are highly specific enzymes involved in the degradation via hydrolysis of the starch molecule, the main natural polymer synthesized by plants, renewable and biodegradable. This substance is reported as an extremely important input, especially in the food and paper industry. However, enzymatic production on an industrial scale reveals high costs, which in turn reflects the final value of the product. The goal of this work was to recover and concentrate amylase with market compatible quality, reducing production expenses through the use of agroindustrial residue, the manipueira. In addition to encouraging agricultural residues application, this work also discusses the application of membrane separation methods, more specifically microfiltration and ultrafiltration in the recovery processes and enzymatic concentration. The process started with the production of amylase from Bacilus subtilis via submerged fermentation in manipueira, the fermented broth being submitted first to the microfiltration process with membrane, aiming to retain suspended material with molecular mass characteristic greater than 500 kDa. The microfiltered permeate gave continuity to the experiment being submitted to the ultrafiltration process, where the objective was to concentrate the amylase, keeping it in the concentrated broth. The enzymatic product was submitted to enzymatic activity tests that showed higher values in the permeate of the microfiltration experiment that used the pressure of 500 N / m² combined the flow of 8 mL / s, reaching 173.9% of recovery, while in the ultrafiltration, higher values of activity were obtained in the concentrate of the experiment that used the pressure of 1000 N / m² combined the flow of 8 mL / s, resulting in 42.66% recovery. The permeate flux was also evaluated along the process, indicating that values between 19.11 and 18.48 were reached using pressures of 500 and 1000 N / m² combined at flow rates 8 and 18 mL / s in the microfiltration, while in the ultrafiltration, the best flows used a pressure of 500 N / m² associated with flow rates of 18 and 28 mL / s. The results corroborate that the use of membranes is an important tool in the concentration and amylolytic recovery, however, microfiltration presents better results both in terms of recovery of enzymatic activity and in relation to permeate flux when related to ultrafiltration procedures.